Analysis Of Individual Investor Behavior At Stock Market Study Group Member Of University In Surakarta Using Analytical Hierarchy Process Method (AHP) - Sari, Cahyani Tunggal; Wardhani, Bernadeta Anindya Nandi (Universitas Semarang, 2018)
Behavioral finance is a new approach to financial markets. Behavioral finance argues that some financial phenomena can be understood sensibly by using a model in which some agents are not entirely rational. The Market Efficiency Theory or known as the EMH (Efficient Market Hypothesis) was introduced by Fama (1970), on the ground EMH said that in an efficient capital market, relevant information will be responded quickly, completely and accurately by the market. If the market is efficient, then all information is reflected in the price. The price will adjust quickly and precisely to new information, and no one